A New Step-Size Skill for Solving a Class of Nonlinear Projection Equations (Journal of Computational Mathematics, 2021)
In this paper, a new step-size skill for a projection and contraction method$^{[10]}$ for linear programming is generalized to an iterative method$^{[22]}$ for solving nonlinear projection equation. For linear programming, our scheme is the same as that of$^{[10]}$. For complementarity problem and related problems, we give an improved algorithm by considering the new step-size skill and ALGORITHM B discussed in [22]. Numerical results are provided.